Pengalaman Perempuan yang Mengalami Sectio Caesarea atas Indikasi pre Eklampsia Berat di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Anisah, Ulfatul; Mursiyam,; Anggraeni, Mekar Dwi (Jurusan Keperawatan FIKES UNSOED, 2010)
Severe Pre Eclampsia (SPE) is one of the main causes factor maternal and perinatal death. Section Caesarea (SC) is the delivery process of the embrio from abdomen intition. SC of SPE can cause many impact whether it phisically and phsicology of the women's during the pregnancy period. The purpose of this research is to know about many kinds of women’s experience that face SC of indications SPE. This research is a qualitatif research with fenomenology approach of women that face SC of SPE indication. The participants of this research is chosen by purposes sampling methods. The data is taken by an interview and field note. The analistic data use Collaizzi's method. This research result is women that face SC of SPE indication has perception about SPE that is, the progress of blood plessure and perception about SC which surgery in stomach to deliver baby because there is disparity in pregnancy the change that face after SC of indication of SPE is like chilled, blurry view, confused, pain for the mobilization, and chest felt congested, fear, change of mood, mounting sensitivity, worry about next pregnancy. The needed requirement is like treatment of partum post, treatment of BBL, drug type information. The expectation of health officer attitude’s is change of health energy when give treatment, comfortable and information about difficulties of pregnancy and hause visiting. The conclusion of this research women that face SC of SPE indication many kinds the change phisically and phsicology. The expectation of health officer attitude’s is change of health energy when give treatment, comfortable and information about difficulties of pregnancy and hause visiting. The support source from husband, health energy and family, and the support types is like instrumental support, emotional, health information and spiritual.